2019
DOI: 10.3390/polym11111886
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Adsorption Behaviors of Amphoteric Polyacrylamide on Cellulose Fibers and Impact on Dry Strength of Fiber Networks

Abstract: Amphoteric polyacrylamide (AmPAM) has been widely used in a variety of industrial areas and the adsorption behavior of AmPAM plays a crucial role in its applications. In this study, a series of AmPAMs with various molecular weights (MW) were synthesized; and their impact on dry strength of fiber networks or paper was assessed. The results showed that the optimal MW of AmPAM for strength enhancement ranged between 300 and 500 k. More importantly, the adsorption behaviors of three typical AmPAM samples on silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Notice that the curves overlapped well in the high force region, indicating that they correspond to the elongation of single-molecule NPAM. 61,62 At low force region (<1000 pN), F−E curves obtained in 0.5 M KAc and in DI water are higher than that obtained in DMSO, while the curve obtained in KSCN shows the opposite trend. Ulteriorly, the stretching energy (defined ΔE) of NPAM in aqueous conditions comparing to that in DMSO (represent the backbone elasticity) were obtained by calculating the area difference between the curves, which can be used to describe the nanomechanical properties of NPAM.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Notice that the curves overlapped well in the high force region, indicating that they correspond to the elongation of single-molecule NPAM. 61,62 At low force region (<1000 pN), F−E curves obtained in 0.5 M KAc and in DI water are higher than that obtained in DMSO, while the curve obtained in KSCN shows the opposite trend. Ulteriorly, the stretching energy (defined ΔE) of NPAM in aqueous conditions comparing to that in DMSO (represent the backbone elasticity) were obtained by calculating the area difference between the curves, which can be used to describe the nanomechanical properties of NPAM.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Adsorption of PEDOT:PSS was found to be a spontaneous reaction driven by entropy gain. Zhang et al (2019) studied the adsorption behavior of amphoteric polyacrylamide (AmPAM) as a papermaking additive on microcrystalline cellulose (MCC) and use QCM-D to monitor the effect of different molecular weights of AmPAM on adsorption in real time. It was concluded that the optimal molecular weight range for increasing the dry strength of paper was between 300k and 500 k.…”
Section: Application Of Qcm-d For Microparticles Adsorption Onto Modi...mentioning
confidence: 99%